Influence of Ru on creep behaviour and concentration distribution of Re-containing Ni-based single crystal superalloy at high temperature - Zhao Guoqi; Tian Sugui; Shu Delong; Tian Ning; Yan Huajin; Wang Guangyan; Liu Lirong (Materials Research Express, 2020)
The influence of Ru on the creep behaviour of a Re-containing Ni-based single crystal alloy at high temperature is investigated by creep capabilities measurement and microstructure evaluation. The creep life of the Re alloy at 1100 °C/137 MPa obtained is 164 h, after added 3.0%Ru, the creep lifetime of 4.5Re/3Ru alloy at the same conditions is 321 h. The deforming characteristic of the alloys during creep is dislocations gliding on γ matrix and climbing over γ ′ phase. And a few dislocations of shearing γ ′ phase may cross-glide for forming Kear-Wilsdorf (KW) locks in Re-containing alloy. While more KW locks reserve in the γ ′ phase of 4.5Re/3Ru alloy. The reason of 4.5Re/3Ru alloy displaying an outstanding properties is put down to more Re, W atoms being distributed in the γ ′/ γ interface to delay dislocations shearing γ ′ phase and depress the sliding and cross-sliding of dislocations. Wherein, the atoms Ru may replace the Al atoms in γ ′ phase, the stronger bonding force between Ru atoms and Re, W, Mo promotes much more ones dissolving into γ ′ phase to delay the diffusion of them, this is deem as an important reason of the Re/Ru alloy displaying an outstanding creep resistance at high temperature.